Intraoperative Sonography During Carotid Endarterectomy: Normal Appearance and Spectrum of Complications. (1st May 2015) - Weinstein, Stefanie; Mabray, Marc C.; Aslam, Riz; Hope, Tom; Yee, Judy; Owens, Christopher
Abstract : Carotid endarterectomy is a commonly performed procedure for prevention of stroke related to carotid stenosis. Intraoperative sonography is used to identify potentially correctable technical defects during carotid endarterectomy. The main risk of endarterectomy is perioperative stroke, and great effort has been put into trying to reduce this risk through various surgical techniques and evaluation of the surgical bed. Postoperative carotid thrombosis, or thombo‐embolization from the arterectomy site, remains a common cause of perioperative stroke and is often related to technical defects in the arterial reconstruction procedure. Re‐exploration and repair of any imperfections have the potential to improve outcomes. Intraoperative imaging can identify potentially occult lesions, provide the option for correction, and thus reduce chance of stroke. Familiarity with the spectrum of intraoperative sonographic findings helps correctly identify residual intimal dissection flaps, plaque, thrombi, and stenosis, which may require immediate surgical revision. Our objective is to illustrate the spectrum of intraoperative findings and their importance.